Hubungan Spiritualitas dengan Stres pada Penderita Hipertensi di Poli Jantung RSU dr. H. Koesnadi-Bondowoso - Muhamad Alfian Adyatma; Murtaqib Murtaqib; Baskoro Setioputro (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
Stress becomes one of the factors causing hypertension. The correlation of stress and hypertension occurs through sympathetic nerve activities, which can gradually increase blood pressure. Spirituality is one of coping to deal with stress. Someone who has a high spiritual level is believed that his belief and relationship with God are better. This study analyzed the correlation between spirituality and stress in hypertension patients at the Cardiology unit of dr. H. Koesnadi Hospital-Bondowoso. The variables were Spirituality and Stress. The research design was observational analytic with a cross-sectional approach with 84 respondents obtained using consecutive sampling technique. The data collection was carried out by giving the Daily Spiritual Experience Scale (DSES) and Perceived Stress Scale (PSS) questionnaire on August 14th-28th 2018. The results of analysis using the Spearman correlation test were p value = 0.001 and r = -0,429 (p <0, 05), indicated a significant correlation between spirituality and stress in hypertension patients. A person who has good spirituality can control his chronic disease and help him to manage his conditions patiently, calmly and can determine his life goals. Suggestions for nurses are to be able to provide motivation to patients to accept the disease and improve adherence to the treatment.